Effect of adding Salicylic acid and Fertilizer on some Anthraqunion Glycosides content in the leaves of Aloe vera L. Cactis - عباس, ابراهيم صالح; جمعة, فاروق فرج; عبد فليح, صباح (Journal of Kerbala for Agricultural Sciences, 2015)
This research was conducted in one of the farms of Horticulture Department/ College of Agriculture/ Baghdad University on Aloe vera L. Cactis plant for the duration 1/9/2012 to 1/11/2013 by adding Salcylic acid at 0, 100, 200 mg. L-1 interacted with a combination fertilizer consist of Humic acid at 0, 1, 2 ml.L-1. And Chemical factorial NPK at 0 and 2gm.Plant-1. To enhanced vegetative growth and their effect on Leaves content of Anthraqunion Glycosides. Results showed that the addition of Salcylic acid caused significantly increased in all Anthraqunion Glycosides except Anthranol while these compounds where increased in all fertilizer combinations, and the highest Values appeared when Salcylic acid interacted with fertilization.